2019
DOI: 10.1177/0743915618820925
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Egocentric Taste Judgments on Stereotyping of Welfare Recipients and Attitudes Toward Welfare Policy

Abstract: Despite the centrality of purchasing behavior and choice to the welfare debate, research has generally understood attitudes toward welfare at a broader level and as a function of rational or deliberative processes (e.g., self-interest, ideology). This project identifies the effect of egocentrism on welfare attitudes, finding that a welfare recipient’s purchase of an item that the participant personally values less (vs. more) leads to increased stereotyping of welfare recipients (e.g., irresponsibility, impulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…These kinds of human in-store interactions could have a more significant impact on low-income consumers receiving federal food assistance than on regular consumers, as there may be a perceived stigma associated with receiving governmental assistance (Baumberg 2016; Rogers-Dillon 1995). For example, participants may be worried about being perceived as lazy (Fox 2004; Gilens 1995) or irresponsible (Shepherd and Campbell 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…These kinds of human in-store interactions could have a more significant impact on low-income consumers receiving federal food assistance than on regular consumers, as there may be a perceived stigma associated with receiving governmental assistance (Baumberg 2016; Rogers-Dillon 1995). For example, participants may be worried about being perceived as lazy (Fox 2004; Gilens 1995) or irresponsible (Shepherd and Campbell 2020).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Some example factors that explain support for redistributive taxes include how the policy is framed, social sampling bias, and respondents' political orientation (Chow & Galak, 2012;Dawtry et al, 2015;McCaffery & Baron, 2006). Other research has examined attitudes toward increases to minimum wage and welfare programs (Brown-Iannuzzi et al, 2017;Henry et al, 2004;Kuziemko et al, 2014;Shepherd & Campbell, 2020), with factors such as stereotypes, egocentric preferences, and respondents' relative wage partly explaining attitudes. Although such research is promising, economic inequality is not solely affected by taxation and welfare programs.…”
Section: What Do These Findings Mean?mentioning
confidence: 99%
“…We provide robust evidence that permissibility does indeed vary systematically for lower-vs. higher-income individuals and explore why these discrepant judgments emerge. Important related work has documented similar negative attitudes toward the purchase decisions of lower-income individuals receiving welfare assistance (4,15,16,25). For example, Olson et al (4) showed that welfare recipients were regarded as less moral for buying ethical goods (e.g., organic foods, ecofriendly cars) than nonwelfare recipients.…”
mentioning
confidence: 99%
“…In the present research, we examine and empirically document such judgments against lower-income individuals' consumption decisions, and contribute to a growing body of work on negative attitudes toward the poor (e.g., refs. 9-15) and their purchase behaviors (4,16), and the broader social consequences of class hierarchies (17)(18)(19)(20)(21). Building on literature about the inferences people make about others' choices (22)(23)(24), we introduce the notion of "permissible consumption," a distinct construct measuring interpersonal judgments about what is acceptable (or not) for others to purchase.…”
mentioning
confidence: 99%